2008
DOI: 10.1002/ange.200800231
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐Resonance‐Enhanced Absorption and Circular Dichroism

Abstract: Kolloidale Ag‐Nanopartikel mit L‐Glutathion‐Beschichtung, die an Biman‐Chromophore gebunden sind, wurden bezüglich ihrer absorptions‐ und fluoreszenzspektroskopischen Eigenschaften sowie ihres Circulardichroismus (CD) untersucht. Die Abhängigkeit der Verstärkung der Spektren durch resonante Ag‐Oberflächenplasmonen von der Wellenlänge und der Partikelgröße spricht für einen elektromagnetischen „Antenneneffekt“.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The latter lies ca. [12][13][14][15][16][17][18][19][20][21] This is typical of surface enhanced Raman or photopolymerization where the metallic structure acts to concentrate the electromagnetic field much like a lens focusing light. From the relative intensities of the dips at 525 nm (S 0 to j S 2 -SP > À ) and at 490 nm (S 0 to S 2 ), it is clear that not all the molecules are strongly coupled and that the S 0 to j S 2 -SP > À absorption coefficient (transition probability) is high.…”
Section: Methodsmentioning
confidence: 99%
“…The latter lies ca. [12][13][14][15][16][17][18][19][20][21] This is typical of surface enhanced Raman or photopolymerization where the metallic structure acts to concentrate the electromagnetic field much like a lens focusing light. From the relative intensities of the dips at 525 nm (S 0 to j S 2 -SP > À ) and at 490 nm (S 0 to S 2 ), it is clear that not all the molecules are strongly coupled and that the S 0 to j S 2 -SP > À absorption coefficient (transition probability) is high.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, colloidal AgNPs coated with GSH were used as electromagnetic antennae. [120] It was shown that the absorption and CD spectra of bimane, a chromophore, were enhanced when attached to NPs. The chromophore absorbs at the surface-plasmon-resonance wavelength of the AgNPs.…”
Section: Chiral Discriminationmentioning
confidence: 99%
“…Research in this area is concentrated around spectroscopy of different plasmon modes7, appearance of hot spots, enhancement of different optical effects by plasmonic fields8, plasmon-to-heat conversion, and a variety of applications related to these effects9. Compared to the large progress in these areas, we are only beginning to understand a variety of chiral effects related to nanoscale plasmonic materials1011121314151617.…”
mentioning
confidence: 99%
“…Chirality of individual NPs can arise from electronic “imprints” of molecules on their surface1617. Different chirooptical effects for plasmonic materials could be unusually strong78111422 and enable several new photonics technologies11723. The fundamental studies and technology of chiral photonics depends on finding new preparative methods for chiral plasmonic enantiomers.…”
mentioning
confidence: 99%